Analisis Tingkat Kepuasan Pelanggan Berdasarkan Kualitas Produk Motor Matic Yamaha Soul GT Pada PT. Yamaha Mataram Sakti Setiabudi Semarang - Tri Handayani; Apriatni Endang Prihatini; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2014)
This research exposed background by wave of globalization that led to the emergence of free competition which make the principals compete in their business. Yamaha was the first company that introduce the motor automatic-based technology. Starting 2005 Yamaha matic motorcycle class become the market leader. However, if viewed developments in the following years after the emergence of other competitors, Yamaha matic market share declined to 2013. In 2013 matic motorcycle Yamaha Soul GT became the best-selling, but sales achievement matic motorcycle Yamaha Soul GT than other series of matic motorcycle Yamaha. In 2014 sales of Yamaha Soul GT also decreased and the sales below Yamaha Mio and Mio GT.The purpose of this research was to determine the level of satisfaction of customers / users Yamaha Soul GT at PT. Yamaha Mataram Sakti Setiabudi Semarang. This type of research is descriptive data capture techniques through questionnaires, interviews and literature study. The sampling technique used purposive sampling. The sample in this study amounted to 81 respondents who are customers of PT. Yamaha Mataram Sakti Setiabudi which uses Yamaha Soul GT. This research uses quantitative and qualitative analysis techniques. Quantitative analysis using the Importance-Perfomance Analysis and Cartesian diagram.The results of this research about average level of customer satisfaction Yamaha Soul GT into the category of content, but the average level of customer expectations on eight dimensions used in this research is higher than the level of performance.Based on the research results, the researchers suggested that the company give more attention to the quality of the engine and the frame on the Yamaha Soul GT and companies need to give attention to the dimensions of durability (Age productive Yamaha Soul GT and resale price of Yamaha Soul GT) so as to improve customer satisfaction.